2022
DOI: 10.1017/ice.2022.88
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to prevent ventilator-associated pneumonia, ventilator-associated events, and nonventilator hospital-acquired pneumonia in acute-care hospitals: 2022 Update

Abstract: The purpose of this document is to highlight practical recommendations to assist acute care hospitals to prioritize and implement strategies to prevent ventilator-associated pneumonia (VAP), ventilator-associated events (VAE), and non-ventilator hospital-acquired pneumonia (NV-HAP) in adults, children, and neonates. This document updates the Strategies to Prevent Ventilator-Associated Pneumonia in Acute Care Hospitals published in 2014. This expert guidance document is sponsored by the Society for Healthcare E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
62
0
22

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 117 publications
(113 citation statements)
references
References 392 publications
0
62
0
22
Order By: Relevance
“…Of note, at the time the survey was conducted antimicrobial mouth rinse was still an accepted element of VAP prevention bundles. Since then, updated Compendium VAP prevention guidelines have been published, which no longer recommend antimicrobial mouth rinse as a preventive measure [ 19 ]. We note also that VAP prevention and surveillance are not nationally mandated in Israel, but are rather prioritized and managed at the institutional level, at the discretion of hospital management.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, at the time the survey was conducted antimicrobial mouth rinse was still an accepted element of VAP prevention bundles. Since then, updated Compendium VAP prevention guidelines have been published, which no longer recommend antimicrobial mouth rinse as a preventive measure [ 19 ]. We note also that VAP prevention and surveillance are not nationally mandated in Israel, but are rather prioritized and managed at the institutional level, at the discretion of hospital management.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, since they cannot be modified, we cannot obtain any impact on these variables to reduce mortality. But, on the other hand, we have found some variables that are feasible to be modified, and they are indwelling time of CL-days, indwelling time of UC-days, MV-utilization ratio, UC-utilization ratio, and implement an evidence-based set of HAI prevention recommendations [36,37]. HAIs in ICUs in Latin America are several times higher than those in high-income countries [12][13][14][15][16][17][18][19], and a greater effort should be made to reduce the rates of HAIs, and thus be able to reduce this high mortality rate.…”
Section: Discussionmentioning
confidence: 99%
“…As HAI rates in Latin America are significantly higher than in the US, there is room for improvement [ 12 19 ]. Based on our findings, it is suggested that we focus on strategies to reduce indwelling time of CL-days, UC-days, MV-utilization ratio, UC-utilization ratio, and implement an evidence-based set of HAI prevention recommendations, such as those recently published by IDSA/SHEA/APIC [ 36 , 37 ]. Also, the high rate of HAIs prevalent in the Latin America [ 12 19 ] can be reduced by utilizing a strategy of monitoring compliance with recommendations and providing performance feedback to healthcare personnel, as demonstrated by INICC in several ICUs of Latin America [ 38 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…is an emerging pathogen. Among gram-positive organisms, MRSA is the major pathogen [ 19 ]. Organisms causing CAUTI are more resistant to antibiotics, and 3% of CAUTI patients are at risk of developing bacteremia.…”
Section: Epidemiologymentioning
confidence: 99%